(untitled) (International journal of medical sciences, 2026)
The review article analyzes the tactics of treating coronavirus infection, examines the influence of microelements zinc and selenium, as well as the macroelement magnesium on the development of the body's immunity, on metabolism, as well as on the course of the COVID-19 disease and the pharmacotherapeutic value of these macro- and microelements in the treatment of COVIDnineteen.